Keanekaragaman Jenis Kelelawar (Chiroptera) di Taman Nasional Kelimutu - Gabriel Alexandro Tonda; Fadlan Pramatana; Mhd Muhajir Hasibuan (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Bats (Chiroptera) are the only type of mammal that can fly. Bats have high mobility in their foraging activities, such as flowers, fruits, nectar, and insects at night. Indonesia has several species of bats that are widely distributed across several major islands, such as Sumatra, Java, Kalimantan, Sulawesi, and Papua. Kelimutu National Park has various potential habitats for flora and fauna that can support the life of bats. Information about bats in Kelimutu National Park is not yet available, so this research was conducted to obtain initial information/data on bat species in Kelimutu National Park. This research aims to describe the level of diversity of bat species (Chiroptera), including species names, local names, and family names, in Kelimutu National Park. This research uses direct observation methods with tools such as harps and mist nets, and vegetation analysis. The results show that the most abundant species is the Nusa tenggara short-nosed fruit bat (Chinopterus nusatenggara), with 35 individuals, and the highest number of findings was in the Wolojita resort with 12 individuals. Meanwhile, the least found species was the wall-roosting mouse-eared bat (Myotis muricola), with a total of 14 individuals found across all five locations, indicating that each location has varying levels of diversity. The bats found in this study have a Least Concern (LC) conservation status, although they are not currently facing serious extinction threats in the wild, it is still important to maintain their habitats to remain stable.